2006
DOI: 10.1007/s10067-006-0389-9
|View full text |Cite|
|
Sign up to set email alerts
|

The levels of sCD30 and of sCD40L in a group of patients with systemic lupus erythematodes and their diagnostic value

Abstract: CD30/CD30L and CD40/CD40L are molecules from the tumor necrosis factor (TNF) superfamily. They have a major effect on communications between the B and T cells, which leads to control of maturation, proliferation, and apoptosis of those cells. The aim of this study was to compare the levels of a soluble form of CD30 (sCD30) and a soluble ligand CD40 (sCD40L) in patients with systemic lupus erythematosus (SLE) (n=65) and healthy controls (sCD30 n=20, sCD40L n=10) with other parameters of SLE activity. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…The interaction between these two molecules provides direct help to T cells for B-cell activation and up-and down regulation of their apoptosis. The impaired interaction CD30.CD30L and CD40/sCD40L leads to severe defects in immunity response, as is shown in various cases as SLE, rheumatoid arthritis, and various tumors [15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The interaction between these two molecules provides direct help to T cells for B-cell activation and up-and down regulation of their apoptosis. The impaired interaction CD30.CD30L and CD40/sCD40L leads to severe defects in immunity response, as is shown in various cases as SLE, rheumatoid arthritis, and various tumors [15].…”
Section: Discussionmentioning
confidence: 98%
“…Both, the receptors and its ligands may be secreted to the body fluids, appearing there as soluble forms. They have a major effect on communications between the B and T cells, which leads to control of maturation, proliferation, and apoptosis of those cells [15]. The biological functions performed by sCD30/sCD30L and sCD40/sCD40L systems have been evaluated throughout numerous studies, yet have not been fully explained.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble CD30 is released from the surface of activated T lymphocytes by a zinc metalloproteinase in response to interaction with positive CD30L cells [8]. By analysing serum CD30s levels using enzyme-linked immunosorbent assay (ELISA), Cifersk a H et al [15] found significant differences in active SLE patients compared to inactive and higher CD30s levels in patients with SLE than in healthy controls. To assess the CD30 expression status on lymphocytes in basal conditions and upon polyclonal stimulation in patients with SLE, a total of 17 inactive SLE and 4 active SLE patients as positive controls were analysed.…”
Section: Discussionmentioning
confidence: 99%
“…The CD30 soluble form (CD30s) released from the surface of peripheral blood cells servers as a marker of active systemic lupus erythematosus (SLE) disease [14,15], being the CD30s levels higher in active rather than inactive SLE patients. However, to date, the expression level of CD30 on the cell surface of CD4 and CD8 lymphocyte subsets in patients with SLE and its role in the pathogenesis are not known.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other studies have reported that levels of sCD30 have important prognostic value for various lymphoproliferative disorders (4,15,22), systemic lupus erythematosus (SLE) (5,7), and leishmaniasis (1,2). The current method for quantitation of sCD30 is the enzyme-linked immunosorbent assay (ELISA), which has good sensitivity and specificity.…”
mentioning
confidence: 99%